From Texas with love - Gutman, Dan (Gutman, Dan. Genius Files, 2015)
Twins Pepsi and Coke McDonald's adventures are far from over, as they find themselves in a clothes dryer, locked in a vapor cabinet, nearly flattened by a cow and poisoned with bowling shoes. They may not make it out of Texas alive.